2008
DOI: 10.1016/j.bmcl.2007.10.100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N-(quinolin-8-yl)benzenesulfonamides as agents capable of down-regulating NFκB activity within two separate high-throughput screens of NFκB activation

Abstract: We describe here a series of N-(quinolin-8-yl)benzenesulfonamides capable of suppressing the NFkappaB pathway identified from two high-throughput screens run at two centers of the NIH Molecular Libraries Initiative. These small molecules were confirmed in both primary and secondary assays of NFkappaB activation and expanded upon through analogue synthesis. The series exhibited potencies in the cell-based assays at as low as 0.6 microM, and several indications suggest that the targeted activity lies within a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In addition, in situ hybridization showed that Lcn2 message was induced in scattered epithelia after inoculation (Figure 6C), typical of ICs. To further examine the interaction between UPEC and CD epithelia, we used an IC line (85,86) and applied heat-killed UPECs (5 × 10 6 CFU; P < 0.005; Figure 6D). The bacteria induced LCN2 expression in an NF-κB-sensitive fashion in the ICs (85,86).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in situ hybridization showed that Lcn2 message was induced in scattered epithelia after inoculation (Figure 6C), typical of ICs. To further examine the interaction between UPEC and CD epithelia, we used an IC line (85,86) and applied heat-killed UPECs (5 × 10 6 CFU; P < 0.005; Figure 6D). The bacteria induced LCN2 expression in an NF-κB-sensitive fashion in the ICs (85,86).…”
Section: Figurementioning
confidence: 99%
“…To further examine the interaction between UPEC and CD epithelia, we used an IC line (85,86) and applied heat-killed UPECs (5 × 10 6 CFU; P < 0.005; Figure 6D). The bacteria induced LCN2 expression in an NF-κB-sensitive fashion in the ICs (85,86). In addition, when we explanted epithelia directly from the medulla of Lcn2-Luc2-expressing kidneys (15,43,45) and treated the cells with living UPEC (P < 0.01; Figure 6E), we visualized the activated LCN2-Luc2 reporter.…”
Section: Figurementioning
confidence: 99%
“…1, 133.5, 133.2, 132.0, 131.5, 131.3, 131.2, 129.4, 127.6, 127.5, 127.2, 126.7, 125.7, 120.9, 118.7. GC-MS (EI) m/z 319 (M + +2, 5), 317 (M + , 13), 218 (25), 7, 142 (64), 140 (5), 116 (10), (100), 89 (6), 75 (6) 9, 145.3, 135.9, 134.5, 132.0, 131.8, 131.3, 129.5, 129.2, 129.1, 127.8, 127.6, 127.5, 127.4, 126.7 1, 141.6, 136.0, 135.0, 132.0, 131.7, 130.7, 130.5, 127.8, 124.6, 117.6, 60.5, 14 6,135.9,135.2,133.7,132.1,131.7,130.7,128.0,118.6,(EI) m/z 317 (M + ,14), 218 (8), 143 (12), 142 (100), 140 (6), 116 (9), 115 (87), 89 (6), 75 (7). CH 3 CN).…”
Section: Table 2 Use Of Visible-led Lights In the Intramolecular Phomentioning
confidence: 99%
“…6, 134.1, 133.2, 132.4, 131.8, 131.1, 128.4, 125.5, 125.4, 121.4, 121.1, 119.8, 20.6. GC-MS , 9), 245 (M + , 69), 181 21, 180 (100), 178 9, 153 6, 152 17, 151 7, 127 5, 90 9, 89 5, 77 11, 76 7, 75 5, 63 6, 51 (5). HRMS (TOF, ESI + ): calcd for C 13 H 11 NNaO 2 S (M+Na) + : 268.0403; Found: 268.0400.…”
Section: Isolation and Identification Of Productsmentioning
confidence: 99%
See 1 more Smart Citation